Use of Agar as a Dental Impression Material - Niha Naveed1 , Kishorekumar S2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Agar hydrocolloid was the first successful elastic impression material to be used in dentistry. It is an organichydrophilic colloid extracted from certain types of seaweed. It is a reversible impression material because ofits property of reversing their physical state, which is reusing the impression material for multiple number ofimpressions. It was initially known as “Negacol”, later termed as “Dentacol” when introduced into dentistry